1987
DOI: 10.1525/ae.1987.14.1.02a00100
|View full text |Cite
|
Sign up to set email alerts
|

convicted by the holy spirit: the rhetoric of fundamental Baptist conversion

Abstract: Born‐again Christian belief follows conversion, an inner transformation that quickens the supernatural imagination. Among fundamental Baptists, rhetoric, not ritual, is the primary vehicle of conversion. Witnesses “speak the gospel,” the ramifying discourse and narrative of Christ. Listeners “come under conviction” as they appropriate the gospel in their inner speech. At “the moment of salvation,” listeners become public speakers of the gospel. They “believe” in the sense of embracing a narrative tradition tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
107
0
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(115 citation statements)
references
References 3 publications
0
107
0
8
Order By: Relevance
“…Existing work on religious conversion, for example, focuses on how religious adherents integrate past affiliations and the conversion experience itself into a coherent and continuous self-story. Narratives have been shown to play a role in both accounting for and in accomplishing religious change [15,16]. Other studies have shown how individuals' self-stories are shaped by conventional patterns of telling the story of conversion in their new religious communities [17][18][19].…”
Section: Religion Narrative and Aspirational Identitiesmentioning
confidence: 99%
“…Existing work on religious conversion, for example, focuses on how religious adherents integrate past affiliations and the conversion experience itself into a coherent and continuous self-story. Narratives have been shown to play a role in both accounting for and in accomplishing religious change [15,16]. Other studies have shown how individuals' self-stories are shaped by conventional patterns of telling the story of conversion in their new religious communities [17][18][19].…”
Section: Religion Narrative and Aspirational Identitiesmentioning
confidence: 99%
“…In orthodox Protestantism "church services and revivals are stripped of overt, imagistic, and sacramental material; relatively little happens visually, and spiritual realities are not communicated through sensuous, nonlinguistic means" ( [49], p. 169). In the INC, though, the lack of overt imagistic material coexists with spiritual realities communicated through nonlinguistic means.…”
Section: Silence and The Embodiment Of Obedience In Religion And Workmentioning
confidence: 99%
“…To reciprocate is only a most welcomed consequence of this deep "change". According to Harding (1987), fundamentalist Baptists in the U.S.A. tend to conceptualize proselytism as 'a change in the heart', while officials place the change of faith on the Word of God ( [49], pp. 168-70).…”
Section: Another Informant Saysmentioning
confidence: 99%
“…Mas acho besteira, o importante é aceitar Jesus". (Ana, há 10 anos na igreja) Considerações Finais 42 A relação com o espaço da cidade tem repercussões no processo de construção da subjetividade, como diversos autores já assinalaram, notadamente Georg Simmel (1971;1987) e toda a tradição de estudos da chamada antropologia urbana (Velho, 1980;1994). O espaço da cidade não somente permite como suscita um trânsito e trocas intensas entre de fiéis de diferentes confissões.…”
Section: Ponto Urbe 1 | 2007 32unclassified
“…Desde a obra de autores clássicos, tais como Max Weber (1980) e Troeltsh (19091983), o paralelo entre o mundo católico e protestante em suas relações com a modernidade tem sido um tema importante na sociologia da religião, e continua recorrente nas discussões atuais (Harding, 1987;Hudson, 1981;Leonard, 1981;Martin, 1990;Novaes, 1985;Rolim, 1985;Saunders, 1993). Mudanças recentes nesses universos religiosos, assim como suas adaptações a diferentes contextos sociais e históricos sugerem que esse tipo de comparação requer uma atualização constante.…”
unclassified